роль отбора в управлении формированием депозитарного фонда ГПНТБ СО РАН (Библиосфера, 2010)
A brief analysis of approaches to understanding the role of selection in managing depository collections' formation and technological decisions permitting to improve the characteristics of the process carried out in the basic stock of SPSTL are given.